Size Reduction and Harmonics Suppression in Microwave Power Dividers: A Comprehensive Review - Roshani, Sobhan; Salah I. Yahya; Ghadi, Yazeed Y.; Roshani, Saeed; Parandin, Fariborz; Yaghouti, Behnam D. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
In this paper, several types of microstrip power divider are studied and compared in terms of harmonics suppression and size reductions. The importance of this research lies in the fact that power dividers are critical components in various communication systems, and their performance directly affects the overall system efficiency. The conventional structure of the power divider has an acceptable performance at operating frequency in terms of excellent output ports isolation, low insertion loss, and high return loss, but occupies large size and passes unwanted signals at higher frequencies along with desired signal without any suppression. Harmonics are popular distortion and has different distortion impacts in many different facilities. Recently, several techniques are introduced to overcome these drawbacks. Applied open stubs, applied resonators, lumped reactive components such as capacitors and inductors, coupled lines, defected ground structure (DGS), and electronic band gaps are common methods, which are widely used to overcome these drawbacks. Finally, the study results show that the resonator-based power dividers and coupled-line-based power dividers have good performances in terms of size reduction and harmonic suppression but increase insertion loss parameter. Furthermore, the lumped reactive component-based power dividers and applied DGS and electromagnetic bandgap cells suppress unwanted harmonics, but they need extra process to fabrication, which is undesirable. Moreover, the open-stub-based power dividers have moderate performance with simple structure, but size reduction and harmonics suppression are not so superior in this method.